# 布尔代数计算器

## 解决方案

$$\color{red}{\left(\overline{\left(\overline{A} + B\right) \cdot \left(\overline{B} + C\right)}\right)} = \color{red}{\left(\overline{\overline{A} + B} + \overline{\overline{B} + C}\right)}$$

$$\color{red}{\left(\overline{\overline{A} + B}\right)} + \overline{\overline{B} + C} = \color{red}{\left(\overline{\overline{A}} \cdot \overline{B}\right)} + \overline{\overline{B} + C}$$

$X = A$应用双重否定（对合）定律$\overline{\overline{X}} = X$

$$\left(\color{red}{\left(\overline{\overline{A}}\right)} \cdot \overline{B}\right) + \overline{\overline{B} + C} = \left(\color{red}{\left(A\right)} \cdot \overline{B}\right) + \overline{\overline{B} + C}$$

$$\left(A \cdot \overline{B}\right) + \color{red}{\left(\overline{\overline{B} + C}\right)} = \left(A \cdot \overline{B}\right) + \color{red}{\left(\overline{\overline{B}} \cdot \overline{C}\right)}$$

$X = B$应用双重否定（对合）定律$\overline{\overline{X}} = X$

$$\left(A \cdot \overline{B}\right) + \left(\color{red}{\left(\overline{\overline{B}}\right)} \cdot \overline{C}\right) = \left(A \cdot \overline{B}\right) + \left(\color{red}{\left(B\right)} \cdot \overline{C}\right)$$

## 回答

$\overline{\left(\overline{A} + B\right) \cdot \left(\overline{B} + C\right)} = \left(A \cdot \overline{B}\right) + \left(B \cdot \overline{C}\right)$